A crying baby: not simply infant colic. (22nd August 2012) - Onesimo, Roberta; Giorgio, Valentina; Monaco, Serena; Fundarò, Carlo
Abstract : Hypertrophic pyloric stenosis is a relatively common condition, but atypical presentations can present a diagnostic challenge. We describe the case of a 9-week-old Latin male infant who presented with a 2-day history of intermittent crying and poor feeding. He was suspected to have intussusception but was affected by and successfully treated for hypertrophic pyloric stenosis. Diagnostic tools of atypical HPS cases are discussed.